Exploring the mechanisms driving elderly Fintech engagement: the role of social influence and the elderly’s digital literacy - Mei, Yi (Frontiers in Psychology, 2024)
Objective: This study aims to investigate the elderly digital engagement (acceptance and utilization of technology), with a focus on the widespread application of financial technology: mobile banking (mbanking). Methods: Guided by social influence theory, the research examines the various social dynamics that encourage elderly engagement with m-banking and the moderating effects of their digital literacy. Data was gathered online utilizing a disjunctive approach and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM).The study reveals that both word-of-mouths (WOMs) and peer engagement significantly shape the elderly's perceived usefulness of the platform, thereby influencing their m-banking engagement. Additionally, the level of digital literacy among older adults was found to impact their perceived usefulness of m-banking services. Interestingly, digital literacy among older adults negatively moderates the positive associations of WOMs and peer engagement on perceived usefulness. Discussion: These insights advance our understanding of how social interactions can steer technological engagement, particularly for the silver generation with diverse levels of digital literacy. As society ages and becomes increasingly digitized, it is imperative to promote digital engagement among the elderly and foster a more inclusive digital environment.